LGG-01. Children with Supratentorial Midline Pilocytic Astrocytomas Exhibit Multiple Progressions and Acquisition of Neurologic Deficits over Time. (3rd June 2022) - Brossier, Nicole; Strahle, Jennnifer; Cler, Samuel; Wallendorf, Michael; Gutmann, David
Abstract: Pilocytic astrocytomas are the most common solid tumor of childhood and can arise anywhere in the central nervous system, including the posterior fossa (pf-PA), supratentorial midline (sm-PA; including optic pathway, hypothalamus, thalamus), and brainstem (bs-PA). Location (sm, bs) has been previously proposed as a prognostic factor for PA, but is difficult to separate from resection status on multivariate analysis. To overcome this limitation, we assembled a large cohort of children (n = 251) with biopsy-proved PA treated at St. Louis Children's Hospital from 2003 – 2021 and analyzed outcomes only in patients with subtotal resection (STR; n = 81). We excluded patients with NF1, as NF1-associated gliomas often display a more indolent clinical course than their counterparts. We identified that children with STR sm-PA had a higher likelihood of multiple progressions compared to children with STR bs-PA and pf-PA. This was associated with worsening neurologic deficits over time, consistent with the sm location as a poor prognostic factor. Furthermore, the only children in our cohort with leptomeningeal dissemination or death harbored sm-PAs. Tumors in this location were also associated with an increased likelihood of non-BRAF-fusion genetic alterations and multiple oncogenic mutations. Overall, these data support location as an independent prognostic factor for PA in cases in which a gross-total resection cannot be achieved. Treating neuro-oncologists may thus wish to consider early intervention rather than watch-and-wait strategies at first progression of STR sm-PA. These patients may also benefit from earlier consideration of molecularly targeted therapy.